E-Leges: Sistem Legalisir Ijazah Berbasis Online Pada Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry - Nur Andula; Bustami Yusuf (Query: Journal of Information Systems, 2018)
Printed documents such as diplomas and transcripts are very easy to do by imitating the form and content of the document. Such fraudulent practices are often passed from the monitoring of the authorities, this is because the agency's diploma checking system still uses manual methods. FTK UINAR, where the legalized certification checking system still uses manual way, so it is possible for irresponsible people to cheat such as forgery of diploma. Based on the problem, required an alternative system that can provide solutions to the problem. The system is a web based system and provide a computerized legalization service. Quick Response (QR) code will be used to facilitate verification of authenticity of the diploma for the institution of diploma user. The development methods that use in this research is prototype method. The result of the research is in the form of online legal certification system system by utilizing QR Code as the service system of alumni for legalizing diploma and transcript, which consists of database design and system design using Unified Modeling Language (UML), as well as the design of the legalized system based diploma online.Keywords: The legalized, Quick Response (QR) Code, Unified Modeling Language (UML), prototype method.